Analisis Zakat Produktif Dalam Pemberdayaan Ekonomi Umat di Lazismu Banyumas - Rahmini Hadi; A'yuni Thuba Hamba Allah (Mabsya: Jurnal Manajemen Bisnis Syariah, 2019)
Zakat is maliyah ijtima’iyyah activity. As the third pillar of Islam, zakat has strategic social purpose regarding to increas such economic welfare of society. through potentiality of national zakat that reach at 217 billion rupiahs in a year, it is able to support and solve some economic problems. However, only 0.2% or around 6 billion of zakat had been collected in every year. This is clearly shown that there is lack of attention toward mechanism and distribution of that fund. Economic empowerment of umat program is one of alternative choices in order to manage fund of zakat which had funded from society intensively. This program relates with the efficient use of zakat in the terms of financial resources regarding to obtain such human welfare. This research is kind of field research with qualitative descriptive approach in order to analyse a productive zakat in terms of economic empowerment of umat in Lazismu Banyumas. In addition, the author uses observation, interview, and document research in order to collect data regarding to make such an academic interpretation which consist of data reduction, data presentation, creating conclusion and verification. Based on analysis and interpretation that had been done, this research delineates that Lazismu Banyumas is utilize the productive zakat program in order to support mustahik through some method such as financing scheme, hibah in the terms of trading tools, also giving such a capital in order to develope their sectors (agriculture, fishery and farm). Therefore, through those programmes there are some mustahik who are succeed which can improve their economic level.